Optimized tacrolimus dosing strategy in kidney transplant recipients receiving nirmatrelvir-ritonavir for COVID-19 - Han Yan; Shanbiao Hu; Hedong Zhang; Yangang Zhou; Rao Fu; Ping Xu; Hualin Cai; Xi Li; Gongbin Lan (PLoS ONE, 2025)
Kidney transplantation recipients (KTRs) represent a vulnerable population for COVID-19 infection and severe disease. Nirmatrelvir-ritonavir has demonstrated efficacy in treating COVID-19 among KTRs, and interacts with tacrolimus leading to a precipitous increase in tacrolimus blood levels when co-administered, which may potentially result in toxicity. To explore a safe strategy for the combination of nirmatrelvir-ritonavir and tacrolimus, we established a new administration strategy to restore tacrolimus after the discontinuation of nirmatrelvir-ritonavir and conducted a real-world retrospective observational cohort study to evaluate its clinical efficacy. In the experimental group, tacrolimus was initiated at 20–25% of the baseline dose 48 hours after the discontinuation of nirmatrelvir-ritonavir, with daily increments of 20–25% until the baseline dose was restored. The patients who did not follow the experimental protocol were included in the control group. Results showed that withholding tacrolimus 12 hours before starting nirmatrelvir-ritonavir maintained tacrolimus blood levels above 83% of the baseline throughout the nirmatrelvir-ritonavir treatment period. Compared with the control group, the experimental group achieved target trough concentrations of tacrolimus more quickly and maintained a higher proportion within the therapeutic range ( p = 0.029), and had significantly lower rates of adverse events ( p = 0.002, OR = 0.308, 95%CI:0.136–0.695). This study provides a safe and effective pharmacological strategy for KTRs infected with COVID-19, allowing the safe co-administration of nirmatrelvir-ritonavir and tacrolimus.